Cancer care in German centers of excellence during the first 2 years of the COVID-19 pandemic - Volker Arndt; Daniela Doege; Stefan Fröhling; Peter Albers; Hana Algül; Ralf Bargou; Carsten Bokemeyer; Martin Bornhäuser; Christian H. Brandts; Peter Brossart; Sara Yvonne Brucker; Tim H. Brümmendorf; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose An increasing number of international studies demonstrate serious negative effects of the COVID-19 pandemic on the timely diagnosis of cancer and on cancer treatment. Our study aimed to quantitatively and qualitatively evaluate the capacities of German Comprehensive Cancer Centers (CCCs) in different areas of complex oncology care during the first 2 years of the COVID-19 pandemic. Methods Prospective panel survey over 23 rounds among 18 CCCs in Germany between March 2020 and June 2022. Results The COVID-19 pandemic substantially affected the oncological care system in Germany during the first 2 years. Persistent limitations of care in CCCs primarily affected follow-up (− 21%) and psycho-oncologic care (− 12%), but also tumor surgery (− 9%). Substantial limitations were also reported for all other areas of multidisciplinary oncological care. Conclusions This study documents the limitations of oncological care during the COVID-19 pandemic and highlights the need to develop strategies to avoid similar limitations in the future.